How to Bridge Cognitive and Cultural Models of Religious Evolution - Jackson, Joshua Conrad (Journal for the Cognitive Science of Religion, 2024)
The scientific study of religion has roots in at least two traditions: a cognitive tradition which typically uses experimental studies to examine the proximal psychological processes underlying religious belief and ritual, and an anthropological tradition which uses historical and ethnographic data to examine how religious systems culturally evolve in social groups. In Religion Evolving, Purzycki and Sosis bridge both traditions and encourage a more integrated evolutionary science of religion. In this essay, I present three suggestions for how to make this science as ambitious and collaborative as possible. These suggestions are: (1) to move beyond straw man debates that pit byproduct models against functional models of religious evolution and acknowledge that these models are compatible from a dual inheritance perspective, (2) to evaluate functionalist claims with caution, recognizing how and when religion is adaptive vs. maladaptive for secular society, and (3) to avoid reductive definitions of religion and embrace religious pluralism. With these lessons in mind, we can usher in a bolder evolutionary science of religion that draws from both cognitive and cultural traditions.